Pengaruh Covid-19, Kualitas Auditor, dan Manajemen Laba terhadap Opini Audit: Studi Empiris pada Perusahaan Sektor Property and Real Estate yang terdaftar di Bursa Efek Indonesia - Rifqi Aulia Lubis; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2023)
This research aimed to examine the effect of covid-19, auditor quality, and earning management on audit opinion. The population in this research are all property and real estate sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique used the purposive sampling. Total sample are 176 companies. The statistical method used logistic regression analysis. The result showed that covid-19 and earning management had no significant effect on audit opinion in property and real estate, and auditor quality had a positive effect on audit opinion in property and real estate sector companies listed on the Indonesia Stock Exchange in 2018-2021.